Pendampingan Dan Pelatihan Baca Tulis Pegon Untuk Memudahkan Anak Memaknai Kitab Di Madrasah Diniyah Sabilal Muhtadin Di Ds. Pulorejo Kec. Ngoro Kab. Jombang - Wirda Lailatul Muqtadiroh; Miksan Ansori (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
Arabic pegon, which is an Arabic writing, script or letter without symbols or punctuation or sound. In the Javanese-Indonesian dictionary, pegon means unusual to pronounce. Another word for "pegon" is gundhil which means bald or plain. In addition, Islamic boarding schools also have a curriculum where most of the learning uses the yellow book, bald and without harakat, so it takes a long time and serious effort to really understand it. There are many sciences that must be passed, starting from writing, reading and even translating it. Therefore, many scholars have made scientific contributions to come up with easy methods so that students can use them well. One of them is the publication of a small and simple book, namely the Pegon Book, a small book that provides instructions and guidance on writing Arabic letters in Javanese (pegon) in a method that is easily understood by students. In this case, the author provides mentoring and training in reading and writing pegons to make it easier for children to interpret the book for the children of Pulorejo Village, whose children do not understand very well about writing pegon. Mentoring and training in reading and writing pegon is very helpful for children in reading books and interpreting books in higher grades. In this mentoring and training process, the enthusiasm of children and the community is needed to make the activity a success.